Anastomotic leakage after elective colorectal surgery: a prospective multicentre observational study on use of the Dutch leakage score, serum procalcitonin and serum C-reactive protein for diagnosis. Issue 3 (5th March 2020) - ,
Abstract: Background: The purpose of this study was to test use of the Dutch leakage score (DLS), serum C-reactive protein (CRP) and serum procalcitonin (PCT) in the diagnosis of anastomotic leakage (AL) after elective colorectal resection in a prospective observational study. Methods: Patients undergoing elective colorectal resection with anastomosis in 19 centres were enrolled over a 1-year period from September 2017. The DLS and CRP and PCT levels were evaluated on postoperative day (POD) 2, POD3 and POD6. Statistical analysis, including determination of the area under the receiver operating characteristic (ROC) curve (AUC), was performed for the primary endpoint of AL; secondary endpoints were morbidity and mortality rates (ClinicalTrials.gov identifier: NCT03560180). Results: Among 1546 patients enrolled, the AL rate was 4·9 per cent. Morbidity and mortality rates were 30·2 and 1·3 per cent respectively. With respect to AL, DLS performed better than CRP and PTC levels on POD2 and POD3 (AUC 0·75 and 0·84), whereas CRP levels were documented with better AUC values on POD6 (AUC 0·81). Morbidity was poorly predicted, whereas mortality was best predicted by PCT on POD2 (AUC 0·83) and by DLS on POD3 and POD6 (AUC 0·87 and 0·98 respectively). Overall, the combination of positive PCT, CRP and DLS values resulted in a probability of AL of 21·3 per cent on POD2, 33·4 per cent on POD3, and 47·1 per cent on POD6. However, the combination of their negative values excluded AL in 99·0 per cent of cases on POD2, 99·3 per cent on POD3, and 99·2 per cent on POD6. Conclusion: DLS and CRP level are good positive and excellent negative predictors of AL; the addition of PCT improved the predictive value for diagnosis of AL. Graphical Abstract: Early diagnosis and treatment of anastomotic leakage (AL) is crucial to limit related mortality. In this prospective 1-year multicentre study of 1546 patients who had an elective colorectal resection with anastomosis, the AL rate was 4·9 per cent. The Dutch leakage score was the best predictor of AL on days 2 and 3 after surgery. Colorectal surgery and markers for leakage